Pengaruh Komunikasi Interpersonal Dan Motivasi Kerja terhadap Kinerja Personil Satuan Reserse Kriminal Di Kepolisian Resort Kota Besar Medan - Hasyimi Hasyimi; Mariatin Mariatin; S. Pasaribu (Universitas Medan Area, 2020)
The purpose of this research is to look at: the influence of Interpersonal Communication And motivation of working Against the performance of the personnel of units of the Criminal Police In Reserse Resort City of Great terrain. The hypothesis put forward is There influence of Interpersonal Communication And motivation of working Against the performance of the personnel of units of the Criminal Police In Reserse Resort City of Big Field Research carried out against Police personnel are part of the 71 Units Reserse criminal, with the total sampling is a sampling technique. Data retrieval method documentation in the form of personnel performance value obtained from Ka urbin ops, and methods of the scale i.e. interpersonal communication and motivation scale work. The results showed; 1.) there was significant influence between the interpersonal communication and motivation of work on performance (Freg coefficient = 48.323; sig 0.000). This indicates that the more good interpersonal communication and the higher motivation of work then the higher performance. Based on the results of this study, it can be stated that the hypothesis presented in this research were declared admissible. 2. interpersonal Communication) and contributed to the motivation of working performance of 58.7%. Separately, interpersonal communication contributes of 56.8% on performance, motivation of working contributes of 26.6% on performance. There is 41.3% of the influence of other variables on performance.